2017
DOI: 10.1016/j.atherosclerosis.2017.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Lipid-modifying efficacy and tolerability of anacetrapib added to ongoing statin therapy in Japanese patients with dyslipidemia

Abstract: Long-term treatment with anacetrapib 100 mg substantially reduced LDL-C, increased HDL-C and was well tolerated in Japanese patients with dyslipidemia (ClinicalTrials.gov number NCT01760460).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 20 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…Furthermore, while the sample sizes of LDL-C and HDL-C GWASs were substantially smaller in East Asians (n = 146,492) compared to European (n = 1,320,016) participants, colocalization analysis clearly indicated the HDL-C signal was shared across ancestries and the LDL-C CETP signal was isolated to European ancestry groups, suggesting that these findings do not simply reflect a lack of sample size, in which case the posterior probabilities would follow a uniform distribution. Nevertheless, randomised controlled trials of anacetrapib conducted in Japanese individuals showed a decreasing effect of CETP inhibition on LDL-C concentration: −38.0% (95%CI −42.4; −33.7) change from baseline 18 , which did not meaningfully differ from the effect observed in European trial participants. This suggests that the lack of LDL-C signal observed in our study, as well as that of Millwood et al, is likely limited to the genetic effects of CETP variants on LDL-C, and does not reflect a fundamental difference in the biology of CETP between European and East Asian individuals.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, while the sample sizes of LDL-C and HDL-C GWASs were substantially smaller in East Asians (n = 146,492) compared to European (n = 1,320,016) participants, colocalization analysis clearly indicated the HDL-C signal was shared across ancestries and the LDL-C CETP signal was isolated to European ancestry groups, suggesting that these findings do not simply reflect a lack of sample size, in which case the posterior probabilities would follow a uniform distribution. Nevertheless, randomised controlled trials of anacetrapib conducted in Japanese individuals showed a decreasing effect of CETP inhibition on LDL-C concentration: −38.0% (95%CI −42.4; −33.7) change from baseline 18 , which did not meaningfully differ from the effect observed in European trial participants. This suggests that the lack of LDL-C signal observed in our study, as well as that of Millwood et al, is likely limited to the genetic effects of CETP variants on LDL-C, and does not reflect a fundamental difference in the biology of CETP between European and East Asian individuals.…”
Section: Discussioncontrasting
confidence: 55%
“…For both diseases, there is however limited information on the potential differences between ancestries of altered lipid metabolism or CETP metabolism specifically. Although approximately 10-30% of participants enroled in CETP-inhibitor trials are of East Asian ancestry 4,18,25 , these studies have not been designed to detect potential differences between ancestry groups, and hence the lack of observed association in these trials does not fully rule out a possible ancestry specific risk increasing effects. Furthermore, it is important to consider to what extent the difference between the effects of CETP on asthma and lung cancer reflect genetic ancestry, or whether these differences might be explained by correlated environmental factors, such as air pollution or life-style choices such as smoking.…”
Section: Discussionmentioning
confidence: 99%
“…A previous examination of obicetrapib in the Netherlands and Denmark which administered 10 mg obicetrapib as monotherapy and in combination with moderate intensity statins, 10 mg rosuvastatin or 20 mg atorvastatin, for 12 weeks reported LDL-C reductions of 45.3%, 63.3%, and 68.2%, respectively 10) . Since then, two phase 2 trials of 10 mg obicetrapib monotherapy administered on top of high-intensity statins, in trials that included <5% of participants have also found similar effects of reducing LDL-C and increasing HDL-C as in non-Japanese populations 18,19) .…”
Section: Discussionmentioning
confidence: 94%
“…It was revealed that there was no significant decrease in the risk of revascularization in the group of CETP inhibitors versus the placebo group (RR = 0.93; 95% CI: 0.81-1.07; p = 0.30; I2 = 74%) (Supplementary Figure S5). There was also no significant difference between the three subgroups for this outcome (p = 0.53) [10,27,29,33,[35][36][37][38]40].…”
Section: Revascularizationmentioning
confidence: 84%
“…The pooled analysis revealed no significant differences in reducing the risk of said outcome between both groups (RR = 0.93; 95% CI: 0.68-1.28; p = 0.66; I2 = 31%) (Supplementary Figure S4). Running the subgroup analyses for this outcome revealed no significant difference (p = 0.40) [10,27,29,33,[35][36][37][38]40].…”
Section: Hospitalization Due To Acute Coronary Syndromementioning
confidence: 88%